Find the solution to ln(3)+ln(x)=ln(6)

To tackle this question, you will need to know about the rules for logarithms. Here we are going to use the product rule, where the addition of these two natural logarithms equals the product of the two compnents of each logarithm. In this case, ln(x)+ln(3)=ln(3x).

You are left with the equation ln(3x)=ln(6). To solve this, you use each exponential as a power of the exponontial function. So the equation becomes eln(3x)=eln(6). Since e is the base of the natural logarithm (ln), this equation simplifies to 3x=6, so x=2

Answered by Tanush M. Maths tutor

14382 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Why do you differentiate in optimisation questions?


How do I find the distance between two point in the plane?


A curve has parametric equations -> x = 2cos(2t), y = 6sin(t). Find the gradient of the curve at t = π/3.


Make a the subject of 3(a+4) = ac+5f .


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences